(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2021)
The text has as aim at analyzing convergences and distances among guidelines produced by the UN and the World Bank, and Brazilian educational policies during the COVID-19 pandemic, especially considering social vulnerability conditions. Research methodological base is documental and organized from documents of digital repositories of international agencies and Brazilian government. Data presented allowed identifying intense international production on educational action planning in the pandemic context, what brings the social vulnerability as key element. However, in Brazilian context is possible observe a gap regarding the theme analyzed, making evident a deliberate responsibility of local subjects by the organization of school activities, and thus prescinding development of national policies which could support these actions, then affecting the right to education of thousands of children and adolescents in 2020. Keywords: Brazilian Educational Policy. Social vulnerability in Brazil. Brazilian Education in Pandemic. COVID-19.